Pengembangan Buku Ajar Matematika Dasar Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika - Vera Rosalina Bulu; Roswita Lioba Nahak (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This research aims to determine the process and results of the development of material-based solutions to improve the mathematical problem-solving skills of elementary school teacher Education Program, Citra Bangsa University. This research is development research with the model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The subject in this study was 2 expert validators and a limited trial subject of second-semester students, elementary school teacher Education, Citra Bangsa University. The study was conducted in the odd semester of 2018/2019. The instrument used is a validity test questionnaire and practicality test. The data analysis techniques used are quantitative and quantifiable descriptive analyses. The results of the development of this resolution-based teaching book are the results of the percentage of basic mathematics teaching book 84% including valid categories, the results of the percentage of test book design validation of 92.5% including a very valid category. Practicality test results showed 88.56% inclusive of very practical category and reliability test result of 0.725 including reliability category.